Incursões na história e memória da comunidade de quilombo de Alto-Alegre - município de Horizonte – CE - Santos, Marlene Pereira dos (2012)
The subject of this dissertation is part of a more general theme concerning whit the black population history in the state of Ceará - Brazil. This is an issue with many aspects and many polemics, such as the existence of black people in the state, but is part of a social attitude which has been the subject of historical research and education in the last 10 years in our graduate program. Alto Alegre is the name of a district of Novo Horizonte city. This city is at the periphery of the large metropolitan region of Fortaleza. The community of maroon Alto Alegre is a black rural community with more than a century of existence, yet the literature contains few references to this existence. The research work with the concepts of afro - dependency and black population based on the historical aspects and not biological. Uses the concept of black rural district and outlines the set of knowledge based on oral history, focusing on the black memory, organized as a collective memory with a focus on culture and cultural heritage of the black population. The research was shaft the economic facts and the social relations established by the community of Alto Alegre in a territory where social groups include blacks, indians and white settlers regarded as represented by the landowners. The study showed a trend of community marked by changes in the forms of work and life prospects, but with the presence of strong cultural identity, interspersed with significant changes in customs and religion. The city of Horizonte is within a region of strong industrialization and geographical constant intervention by the state through the construction of large works such as the BR-116, and channels of integration and the worker.